Herbacetin Broadly Blocks the Activities of CYP450s by Different Inhibitory Mechanisms - Qian, Jianchang; Li, Yinghui; Zhang, Xiaodan; Chen, Daoxing; Han, Mingming; Xu, Tao; Chen, Bingbing; Hu, Guoxin; Li, Junwei (Planta Medica, 2021)
Herbacetin is a bioactive flavanol compound that has various pharmacological effects. However, the pharmacokinetic characteristics have not been thoroughly investigated. Previously, we screened a natural compound library and identified herbacetin as a potent CYP blocker. Herein, we aimed to mechanistically determine the inhibitory effects of herbacetin on CYP450 and its potential application. A human liver microsome incubation system was developed based on a UPLC-MS/MS method. Moreover, an in silico docking assay and a human CYP recombinase reaction system were developed and used to investigate binding affinity and inhibitory efficacy. Subsequently, the effects of the combination of herbacetin and sorafenib on HepG2 cells were assessed by MTT and immunoblotting assays. The concentration of sorafenib and its main metabolite were measured by UPLC-MS/MS after incubation with or without herbacetin. As a result, we found herbacetin almost completely inhibited the functions of major CYPs at 100 µM. Moreover, through analysis of the structure-activity relationship, we found 4-, 6-, and 8-hydroxyl were essential groups for the inhibitory effects. Herbacetin inhibited CYP3A4, CYP2B6, CYP2C9, and CYP2E1 in a mixed manner, but non-competitively blocked CYP2D6. These results are in good agreement with the recombinase reaction in vitro results, with an IC50 < 10 µM for each tested isoenzyme. Interestingly, the stimulatory effects of sorafenib on HepG2 cell apoptosis were significantly enhanced by combining with herbacetin, which was associated with increased sorafenib exposure. In summary, herbacetin is a potent inhibitor of a wide spectrum of CYP450s, which may enhance the exposure of drugs in vivo.
Keywords: herbacetin; mixed inhibition; non-competitive inhibition; CYP450s; HepG2